Study of Some Hormonal and Genetic Variants in Women with Polycystic Ovaries Syndrome in Baghdad City/Iraq - Noor Thamer Hamood Al-Dolaimy (Journal of Global Pharma Technology, 2018)
The study was carried out to determine the impact of the levels of sexual hormones represented by (LH, FSH, Prolactin and Testosterone) and also to assess the damage in the genetic material of DNA (comet assay) through the standards which are represented by (Tail length, DNA in tail, and Tail moment). Hormonal levels were examined on the second day of the menstrual period for 50 women infected with polycystic ovary syndrome (patients) and 20 women without polycystic ovary syndrome (control). In addition to that, the hereditary caudate test was tested for 34 patients with polycystic ovary syndrome compared to 50 women in the control group. The results showed a significant increase in the level of Testosterone and a significant decrease in the level of Prolactin hormone levels of LH and FSH hormones were within normal values as well as the genetic instability of DNA is more common in women with polycystic ovary syndrome PCOS compared with control group women.Keywords: Sexual hormones, PCO and comet assay.